Thermal Spray Coatings for Electromagnetic Wave Absorption and Interference Shielding: A Review and Future Challenges. Issue 7 (1st April 2022) - Faisal, Nadimul Haque; Ahmed, Rehan; Sellami, Nazmi; Prathuru, Anil; Njuguna, James; Venturi, Federico; Hussain, Tanvir; Nezhad, Hamed Yazdani; Katiyar, Nirmal Kumar; Goel, Saurav; Upadhyaya, Hari; Joshi, Shrikant; et al.
Abstract : This review aims to consolidate scattered literature on thermally sprayed coatings with nonionizing electromagnetic (EM) wave absorption and shielding over specific wavelengths potentially useful in diverse applications (e.g., microwave to millimeter wave, solar selective, photocatalytic, interference shielding, thermal barrier‐heat/emissivity). Materials EM properties such as electric permittivity, magnetic permeability, electrical conductivity, and dielectric loss are critical due to which a material can respond to absorbed, reflected, transmitted, or may excite surface electromagnetic waves at frequencies typical of electromagnetic radiations. Thermal spraying is a standard industrial practice used for depositing coatings where the sprayed layer is formed by successive impact of fully or partially molten droplets/particles of a material exposed to high or moderate temperatures and velocities. However, as an emerging novel application of an existing thermal spray techniques, some special considerations are warranted for targeted development involving relevant characterization. Key potential research areas of development relating to material selection and coating fabrication strategies and their impact on existing practices in the field are identified. The study shows a research gap in the feedstock materials design and doping, and their complex selection covered by thermally sprayed coatings that can be critical to advancing applications exploiting their electromagnetic properties. Abstract : This is an extensive review on the application of thermally sprayed coatings with electromagnetic wave (nonionizing) absorption and shielding characteristics over specific wavelengths (e.g., microwave to millimeter wave, solar selective, photocatalytic, interference shielding, thermal barrier heat/emissivity). Further advances could be surged by considering the usage of the range of feedstock composites and hybrid materials to achieve electromagnetic distinctiveness of materials.